Society, medicine, and religion in the sacred tales of Aelius Aristides - Israelowich, Ido, 1972- (Mnemosyne, Supplements, 2012)
Aelius Aristides' Sacred Tales offer a unique opportunity to examine how an educated man of the Second Century CE came to terms with illness. The experiences portrayed in the Tales disclose an understanding of illness in both religious and medical terms. Aristides was a devout worshipper of Asclepius while at the same time being a patient of some of the most distinguished physicians of his day. This monograph offers a textual analysis of the Sacred Tales in the context of the so-called Second Sophistic; medicine and the medical use of dream interpretation; and religion, with particular emphasis on the cult of Asclepius and the visual means used to convey religious content.